Quality of Life among HIV Patients with NCDs Receiving Antiretroviral Therapy in Wakiso District, Uganda: Exploring Key Determinants - Christopher Ddamulira; James Wanzima; Lawrence Sserwanga; Eria Muwanguzi; Frank Pio Kiyingi; Stephen S Kizza (African Health Sciences, 2025)
Background: Uganda, like many other nations, faces a double burden of communicable and non-communicable diseases due to the severe impacts of HIV, antiretroviral therapy, and the increasing number of HIV-positive individuals. Objective: To determine the factors that influence the quality of life among HIV patients with NCDs receiving antiretroviral therapy in Wakiso District, Uganda. Methods: A cross-sectional survey was conducted in Wakiso, Uganda, among HIV patients with NCDs receiving antiretroviral therapy and drug refills from Community Drug Distribution Points (CDDP). 219 participants completed questionnaires between November 2019 and December 2020. The factors assessed as predictors included health promotion, community support system, patient monitoring, age, sex, education level, and marital status. The diagnosis of NCDs was based on documented evidence ofiabetes Mellitus (DM) and Hypertension (HT); fasting blood sugar >7.0 mmol/L (126 mg/dl) for DM, and blood pressure > 140/90mmhg for HT. Data analysis included descriptive statistics, path analysis, and Structural Equation Modeling (SEM), which were used to verify and test the model. Results: The research found that most HIV patients were female (61.6%), aged 40 or older (94.5%), with secondary school or less education (69.4%). 54.8% were single. Community-based NCD services, such as health promotion (β=0.58, P=0.006), community support system (β=0.24, p<0.001), and patient monitoring system (β=0.46, p<0.001), directly influenced the quality-of-life improvements, along with other factors like education level (β=0.76, p<0.001) and marital status (β=0.57, P=0.002). Conclusion: The quality of life for HIV-positive individuals with NCDs in Wakiso district requires strengthening community-integrated HIV-NCD interventions to improve the overall quality of life for these individuals.
Keywords: Community; Non-Communicable Diseases; Services; Quality of Life; HIV; People Living with HIV; Uganda